(untitled) (Journal of the College of Education for Women, 2019)
The archaeological and religious sites play a prominent role in the rest of the other tourist activities as cultural and spiritual needs that can not be dispensed with. Archaeological sites represent cultural origins of the nation. Religious sites represent the state of man’s orientation to God in places of worship . The focus was on the city of Babylon because it is an ancient city and tourist because of its characteristics and elements. The importance of the city of Babylon is illustrated by highlighting its archeological and religious status through its geographical distribution. This gives the subject special importance for the purpose of knowing the city’s important sites. And come out with a number of results and a set of recommendations to overcome the obstacles facing archaeological and religious tourism in the city of Babylon through interviews with tourists and poll their views on these sites. In order to benefit from them and to take them in order to improve the reality of these sites, through which a questionnaire was submitted to a group of researchers number (200) researchers, and the purpose of the questionnaire to identify the extent of the impact of archaeological sites and religious to improve the economic situation , The results of the study showed that all the paragraphs in both sites had a significant effect on improving the economic, social and psychological situation of the city’s population. The paragraphs scored more than the percentage weight of (66%) and the weighted average (2) With the opinion of tourism economists that the archaeological sites of great importance in attracting the population, and improve the economic situation, and thus improve the psychological factor for them.